Sr Examen

Expresión (y&xvx¬z)(xv¬y&z(zv¬x&y))

El profesor se sorprenderá mucho al ver tu solución correcta😉

    Solución

    Ha introducido [src]
    ((x∧y)∨(x∧(¬z)))∧(x∨(z∧(¬y)∧(z∨(y∧(¬x)))))
    (x(z¬y(z(y¬x))))((xy)(x¬z))\left(x \vee \left(z \wedge \neg y \wedge \left(z \vee \left(y \wedge \neg x\right)\right)\right)\right) \wedge \left(\left(x \wedge y\right) \vee \left(x \wedge \neg z\right)\right)
    Solución detallada
    (xy)(x¬z)=x(y¬z)\left(x \wedge y\right) \vee \left(x \wedge \neg z\right) = x \wedge \left(y \vee \neg z\right)
    z¬y(z(y¬x))=z¬yz \wedge \neg y \wedge \left(z \vee \left(y \wedge \neg x\right)\right) = z \wedge \neg y
    x(z¬y(z(y¬x)))=x(z¬y)x \vee \left(z \wedge \neg y \wedge \left(z \vee \left(y \wedge \neg x\right)\right)\right) = x \vee \left(z \wedge \neg y\right)
    (x(z¬y(z(y¬x))))((xy)(x¬z))=x(y¬z)\left(x \vee \left(z \wedge \neg y \wedge \left(z \vee \left(y \wedge \neg x\right)\right)\right)\right) \wedge \left(\left(x \wedge y\right) \vee \left(x \wedge \neg z\right)\right) = x \wedge \left(y \vee \neg z\right)
    Simplificación [src]
    x(y¬z)x \wedge \left(y \vee \neg z\right)
    x∧(y∨(¬z))
    Tabla de verdad
    +---+---+---+--------+
    | x | y | z | result |
    +===+===+===+========+
    | 0 | 0 | 0 | 0      |
    +---+---+---+--------+
    | 0 | 0 | 1 | 0      |
    +---+---+---+--------+
    | 0 | 1 | 0 | 0      |
    +---+---+---+--------+
    | 0 | 1 | 1 | 0      |
    +---+---+---+--------+
    | 1 | 0 | 0 | 1      |
    +---+---+---+--------+
    | 1 | 0 | 1 | 0      |
    +---+---+---+--------+
    | 1 | 1 | 0 | 1      |
    +---+---+---+--------+
    | 1 | 1 | 1 | 1      |
    +---+---+---+--------+
    FNC [src]
    Ya está reducido a FNC
    x(y¬z)x \wedge \left(y \vee \neg z\right)
    x∧(y∨(¬z))
    FNCD [src]
    x(y¬z)x \wedge \left(y \vee \neg z\right)
    x∧(y∨(¬z))
    FNDP [src]
    (xy)(x¬z)\left(x \wedge y\right) \vee \left(x \wedge \neg z\right)
    (x∧y)∨(x∧(¬z))
    FND [src]
    (xy)(x¬z)\left(x \wedge y\right) \vee \left(x \wedge \neg z\right)
    (x∧y)∨(x∧(¬z))